Relationships Among Retinal Nerve Fiber Layer Thickness, Vascular Endothelial Growth Factor, and Cognitive Impairment in Patients with Schizophrenia - Liu Y; Chen J; Huang L; Yan S; Bian Q; Yang F (Neuropsychiatric Disease and Treatment, 2021)
Yanhong Liu,1,2 Jingxu Chen,1,2 Lvzhen Huang,3 Shaoxiao Yan,1,2 Qingtao Bian,1,2 Fude Yang1,2 1Huilongguan Clinical Medical School, Peking University, Beijing, People’s Republic of China; 2Beijing Huilongguan Hospital, Beijing, People’s Republic of China; 3Ophthalmology Department, People’s Hospital of Peking University, Beijing, People’s Republic of ChinaCorrespondence: Fude YangHuilongguan Clinical Medical School, Peking University, Nandian, Road, Changping District, Beijing, 100096, People’s Republic of ChinaTel +86-10-83024251Fax +86-10-83024302Email yangfd2021@163.comBackground: Studies have suggested retinal nerve fiber layer (RNFL) involvement in the pathogenesis of schizophrenia. Additionally, research has shown that vascular endothelial growth factor (VEGF) potentially contributes to the pathophysiology of psychiatric disorders. Therefore, this study aimed to investigate VEGF, RNFL, and correlations with cognitive impairments in schizophrenia patients.Methods: Patients with schizophrenia (n = 138) were compared to healthy controls (n = 160). RNFLs were measured with optical coherence tomography (OCT). The Stroop color and word test (SCWT) was used to evaluate neurocognition. Blood samples were collected to measure VEGF. SPSS 20.0 was used to perform analysis of covariance, t-tests, partial correlation analysis, and linear regression.Results: Thinner RNFLs were found in schizophrenia patients (p < 0.001). RNFL showed a significant correlation with SCWT scores (all p < 0.05). Serum level of VEGF was lower in patients with schizophrenia (p = 0.010). Total and inferior RNFL thicknesses of right eyes were positively correlated to VEGF level (RNFL total thickness p = 0.032, inferior thickness p = 0.014).Total RNFL thicknesses were shown to be reduced following a prolonged duration of illness (both p < 0.01).Conclusion: These findings suggest that patients with schizophrenia have degeneration with RNFL thickness following illness duration, which may contribute to neurocognitive impairments observed in schizophrenia. VEGF is speculated to play some important role on RNFL degeneration with schizophrenia patients.Keywords: RNFL, VEGF, cognitive impairment, schizophrenia